ANALISIS STRATEGI PEMASARAN PADA UD. METE MUBARAQ LOMBE KENDARI - Zainuddin, Muhammad Zabir; Utha, Rasidin; Ijar, La (Sultra Journal of Economic and Business, 2023)
Marketing strategy is a form of plan that is decomposed in the field of marketing. In order for the company to remain able to compete with other companies that issue substitute products, the company's management must be able to manage the company well. So that existing consumers or customers do not switch to other companies. As a mainstay commodity for Sulawesi Tnggara, cashew has good prospects in the future to fill local, national and international markets. Mete Mubaraq produces various processed cashew nuts which have different flavors and characteristics from other business competitors. In addition to the flavors and characteristics offered, UD.Mete Mubaraq Lombe Kendari also provides guarantees to consumers because every product that is marketed has legality from the government (PIRT) and passes a verification process from the Health Service so that the quality and safety of its products can be guaranteed. In addition to direct sales, UD.Mete Mubaraq Lombe Kendari also made a breakthrough by conducting online marketing. It is known that the sales volume of processed cashew products at UD. Mete Mubaraq Lombe Kendari over the last 5 years has tended to increase. This study aims to determine the marketing strategy at UD. Mete Mubaraq Lombe Kendari. This study uses SWOT analysis as a data analysis consisting of an analysis of internal and external conditions. The research results show that the strategy used by UD. Mete Mubaraq Lombe Kendari, namely by providing various types of products, both their own products and products from small and medium enterprises (SMEs) in Sulawesi Tenggara Province.